The influences of urbanization on breeding behavior of American bullfrog (Aquarana catesbeiana) in South Korea - Ji-A. Lee; Md Mizanur Rahman; Seung-Ju Cheon; Amaël Borzée; Ha-Cheol Sung (PLoS ONE, 2025)
Urbanized areas often exhibit high levels of anthropogenic noise, which can mask or interfere with animal communication signals, especially those that use sound to communicate, making it challenging for individuals to detect and interpret acoustic cues. While calling is crucial for anuran breeding and communication, the coping mechanisms of city dwelling and cosmopolitan species in urbanized environments remain understudied. Given that invasive species have higher environmental adaptability than native species (because of habitat specificity and environmental sensitivity), we studied the calling patterns of the invasive American bullfrog (Aquarana catesbeiana) in different levels of urbanized areas in South Korea. In our study, we found an early onset of calling activities in urbanized A. catesbeiana populations, which suggests a change induced by factors related to urbanization on breeding phenology. Additionally, urban populations show more intense diurnal calling activities but shorter breeding periods than non-urban populations. The results indicate water temperature and urban noise as the leading factors influencing calling activities in A. catesbeiana. Urbanization induced changes in breeding and calling activities might have facilitated A. catesbeiana to invade and establish populations outside their natural ecological niches. Thus, this study sheds light on the effect of urbanization on frog breeding activities and how an invasive species copes with modified environments in new areas.